Second Trimester Uterine Artery Doppler Velocimetry and Serum Lipids for Prediction of Pre-Eclampsia - V., Saini; A., Maitra; M., Gupta (International Journal of Innovative Research in Medical Science, 2019)
Background: Reliable markers for prediction and prevention of pre-eclampsia to reduce its associated maternal and perinatal morbidity are lacking. Aim and objectives: To evaluate uterine artery doppler velocimetry and serum lipids in second trimester of pregnancy for prediction of gestational hypertension and pre-eclampsia. Methods: One hundred healthy and normotensive women were enrolled in 2nd trimester of pregnancy. Presence of notching in uterine artery doppler on USG and serum lipid levels were recorded. All women were followed till term/delivery to see development of pre-eclampsia / gestational hypertension later. Results: Absence of diastolic notch in 2nd trimester USG, serum triglycerides levels of <150 mg/dL and serum LDL levels of <100 mg/dL in 2nd trimester of pregnancy were found to have a good negative predictive value of 96.6%, 96.3%, 92.7% for later development of GH/PE. Conclusion: Absent diastolic notch, serum triglycerides <150mg/dL and LDL <100 mg/dL in 2nd trimester of pregnancy can be used to stratify women with low risk pregnancy.